Gaining Greater Adherence from Patients for Amplification - Kasewurm, Gyl A. (Seminars in Hearing, 2019)
Every audiology curriculum features coursework and clinical practicum experiences on the knowledge and skills necessary to complete a basic audiological evaluation, diagnose the source of any abnormalities, and a plan for intervention. More advanced coursework typically includes information on balance disorders, newborn infant hearing screening, hearing conservation, amplification, and other electrophysiological tests. In addition, most programs include at least one course on the basic management principles on how to start and maintain a private practice in audiology. However, educational programs rarely include any type of coursework on how to handle common objections to obtaining help in the form of amplification. This is rather surprising considering that more than 90% of patients whom an audiologist evaluates have sensory neural hearing loss where the primary treatment is amplification, except for people with severe hearing losses who are candidates for cochlear implants. This lack of training and experience often leaves clinicians intimidated by common objections to treatment involving purchasing amplification. This article will discuss common objections that patients voice each day to obtaining amplification and will offer possible solutions.
Keywords: hearing aids; objections; patient adherence